Survey of Family Reproduction Objectives in Independent Midwife Practice in Bireuen District - Raudhati, Sri; Agustina, Agustina (Universitas Teuku Umar, 2024)
Family Planning (FP) is a government program designed to balance needs and population. Couples who use FP usually have their own goals, including postponing pregnancy, spacing pregnancies, or limiting pregnancies. The purpose of this study was to see the reproductive goals of families in independent practice of midwife Bireuen Regency. The type of research used is descriptive correlation, which was conducted from May to June 2024. The research instrument used was google form. The research sample was collected using a total sampling technique with a sample size of 32 respondents. The analysis technique in this study used univariate and bivariate analysis using the chi-square test. Data processing was carried out through the stages of coding, data tabulation, data analysis, and data interpretation. The results of this study showed that there is a relationship between the age of the respondent's last child and the family's reproductive goals (p value 0.024), the reproductive goals of respondents in Bireuen Regency were mostly to space pregnancies (75%), and the type of contraception used most was the 3-monthly injection type (50%). From the results of this study, it is expected that fertile age couple needs to improve knowledge and good health behavior, especially actively participating in obtaining family planning services that are in accordance with the needs and reproductive goals of each family to regulate pregnancy which can improve maternal health.